Diversity of cave-dwelling pseudoscorpions from eastern Yunnan in China, with the description of eleven new species of the genus Lagynochthonius (Pseudoscorpiones, Chthoniidae) - Hou, Yanmeng; Gao, Zhizhong; Zhang, Feng (Zootaxa, 2022)
Eleven new Lagynochthonius species from twelve karst caves of eastern Yunnan are described, including detailed diagnosis and illustrations: L. crassus sp. nov. from Unnamed Cave 1 (Maguan County), L. fengi sp. nov. from Unnamed Cave 2 (Yanjin County), L. magnidentatus sp. nov. from Xiao Cave (Fuyuan County), L. minimus sp. nov. from Yanfen Cave and Cizhu Cave (Xichou County), L. retrorsus sp. nov. from Qinglong Cave (Daguan County), L. serratus sp. nov. from Unnamed Cave 3 (Malipo County), L. spinulentus sp. nov. from Yingshan Cave (Zhenxiong County), L. xiaolinensis sp. nov. from Dayan Cave (Zhenxiong County), L. xibaiensis sp. nov. from Hama Cave (Zhenxiong County), L. xinjiaoensis sp. nov. from Yueliang Cave (Fuyuan County), L. yaowangguensis sp. nov. from Unnamed Cave 4 (Malipo County). An identification key to all known Lagynochthonius species from China is also provided.